FATWA ULAMA TENTANG HUKUM NIKAH MISYA>R PERSPEKTIF MAQA>S}ID SHARI>’AH - Mas adah, Mas adah (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2021)
Misyar marriage is a model of marriage which can be defined as an official marital, relationship between a man and a woman, in which the woman waives some of the rights she would have in a normal Islamic marriage. The muslim scholars have difference opinion about the law of the such marriage. Like any other isues in Islam, it has been a point of controversy and argument, especially among theologians. In this case, some allow, some prohibit and some others are in quo status called tawaqquf in deciding the rule and regulation of such marriage. This study examines the opinions of contemporary muslim scholars based on maqa>s}id shari>’ah perspective, to see which opinion should be prioritized and selected by considering aspects of maqa>sid shari>’ah in connection with marital contexts, and considering its benefits and harms as a result of the maqa>s}id shari>’ah. The method used in this study was library research or text study (study of documents). The results of this study concluded that the banning of misya>r marriage -certaintly in the context of Indonesian society – was mostly in line with maqa>sid shari>’ah in a broad sense, that is, to achieve its benefits and pre-vent its disadvantages. (yang dikurung boleh dihilangkan sekedar tambahan)